Induction of cytochrome P450 via upregulation of CAR and PXR: a potential mechanism for altered florfenicol metabolism by macranthoidin B in vivo - Li, Si-cong; Wang, Bin; Zhang, Min; Yin, Qin; Yang, Zi-yi; Li, Xu-ting; Liang, Ge (Frontiers in Pharmacology, 2024)
Introduction Macranthoidin B (MB) is a primary active component of Flos Lonicerae. In Chinese veterinary clinics, Flos Lonicerae is frequently used in combination with florfenicol to prevent and treat infections in livestock and poultry. However, potential interactions between Flos Lonicerae and florfenicol remain unclear. To systematically study these interactions, it is crucial to investigate the individual phytochemicals within Flos Lonicerae. Therefore, MB was selected for this study to assess its effect on the pharmacokinetics of florfenicol in vivo and to explore the underlying mechanisms involved. Methods Male Sprague-Dawley rats were administered MB (60 mg/kg BW) or sterile water orally for 7 consecutive days. On the 8th day, a single oral dose of florfenicol (25 mg/kg BW) was given. Florfenicol pharmacokinetics were analyzed using ultra-high performance liquid chromatography. The hepatic expression levels of cytochrome P450 (CYP1A2, CYP2C11, CYP3A1), UDP-glucuronosyltransferase (UGT1A1), P-glycoprotein (P-gp), and nuclear receptors, including constitutive androstane receptor (CAR), pregnane X receptor (PXR), and retinoid X receptor alpha (RXRα), were quantified via reverse transcription-quantitative polymerase chain reaction and Western blotting (WB). Hepatic CYP1A2 and CYP2C11 activities were measured using a cocktail method. Additionally, the subcellular expression and localization of CAR, PXR, and RXRαin hepatocytes was assessed using WB and immunofluorescence staining. Results MB significantly reduces the AUC(0-∞) and MRT(0-∞) of florfenicol. MB also markedly upregulates the mRNA and protein expression of hepatic CYP1A2 and CYP2C11, along with their catalytic activities. Substantial upregulation of CAR and PXR proteins occurs in the hepatocyte nucleus, along with significant nuclear colocalization of the transcriptionally active CAR/RXRα and PXR/RXRαheterodimers, indicating MB-induced nuclear translocation of both CAR and PXR. Discussion These findings suggest that MB-induced alterations in florfenicol pharmacokinetics, particularly its accelerated elimination, may be due to increased expression and activities of CYP1A2 and CYP2C11, with CAR and PXR potentially involved in these regulatory effects. Further investigation is yet needed to fully elucidate the clinical implications of these interactions concerning the efficacy of florfenicol in veterinary medicine.